Integridade superficial de Inconel 718 fresado com ferramenta de metal duro em diferentes condições de corte - Oliveira, André Rezende de Figueiredo (2021)
Nickel alloys have good oxidation resistance, excellent mechanical resistance at high temperatures, high creep resistance and high fatigue resistance. For this reason, they are used in the manufacture of structural components in the aerospace industry. These characteristics are responsible for their low machinability. Surface integrity analyzes and residual stresses are topics widely studied to avoid structural failures of the aircraft. Residual stresses are present in all mechanical components subjected to manufacturing processes (thermal and mechanical). This work contributes to the advancement of research related to the influence of the evolution of the wear of carbide tools on the surface integrity of the Inconel 718 alloy in the end milling process. Tests were carried out under finishing, moderate and roughing machining conditions. Tools with different stages of flank wear were used. During the tests, the machining force, power consumption and cutting temperature were measured, the latter using a thermal camera and thermocouples welded in the vicinity of the cutting zone. In the machined parts were measured the surface roughness, hardness, microhardness, and residual stress analyzes obtained through X-Ray diffraction. Two mathematical models were developed to quantitatively describe the surface integrity of the Inconel 718 alloy. Optical microscopy, scanning electron microscopy and dispersive energy analyses were performed on the tools. The analysis of the results showed that the tool wear negatively influences the surface integrity, with the residual stresses varying between compressive and tensile stresses. The results of this work showed a direct relationship between tool wear and increased strength and temperature in the cutting zone. In conclusion, the thermal effect is related to the wear level of the tools that modifies the surface integrity of the material.